Apresente uma derivação à extrema esquerda (DEE) da sentença x = (a - b) * c + d sobre a gramática a seguir.
G = ({A, E, T, F, V}, {a, b, c, d, x, =, +, -, *, /, (, )}, P, A)
P = {< A > -> < V > = < E >
< E > -> < E > + < T > | < E > - < T > | < T >
< T > -> < T > * < F > | < T > / < F > | < F >
< F > -> ( < E > ) | < V >
< V > -> a | b | c | d | x }
< A >
< V > = < E >
x = < E >
x = < E > + < T >
x = < T > + < T >
x = < T > * < F > + < T >
x = < F > * < F > + < T >
x = ( < E > ) * < F > + < T >
x = ( < E > - < T > ) * < F > + < T >
x = ( < T > - < T > ) * < F > + < T >
x = ( < F > - < T > ) * < F > + < T >
x = ( < V > - < T > ) * < F > + < T >
x = ( a - < T > ) * < F > + < T >
x = ( a - < F > ) * < F > + < T >
x = ( a - < V > ) * < F > + < T >
x = ( a - b ) * < F > + < T >
x = ( a - b ) * < V > + < T >
x = ( a - b ) * c + < T >
x = ( a - b ) * c + < F >
x = ( a - b ) * c + < V >
x = ( a - b ) * c + d